Gambaran Pengetahuan Orang Tua Tentang Stimulasi Dini Perkembangan Balita (Usia 12-59 Bulan) - Haryanti Haryanti; Mefrie Puspita; Meinarisa Meinarisa (STIKes Karsa Husada Garut, 2021)
ABSTRACT Background Stimulation of growth and development of toddlers is very important given by parents. If the stimulation is inadequate, the growth and development of children under five will be disrupted. Children aged 12-59 months need stimulation to optimize development. One of the causes of delayed child development is parents' ignorance of the importance of developmental stimulation. This study aims to describe the knowledge of parents about the early stimulation of toddler development (aged 12-59 months). Methods: This research is a quantitative descriptive study. The population in this study were all parents who have toddlers aged 12-59 months in the Kenali Besar Public Health Center working area as of October 2019, totaling 3369 people. The sample in this study were 97 people who were taken by accidental sampling technique. This research was conducted on 3 to 18 August 2020 in the Work Area of ​​the Kenali Besar Community Health Center, Jambi City. The data was collected using a questionnaire sheet and the results of this study were analyzed univariately. Results: The results of the univariate analysis showed that there were 52 (53.6%) respondents who had knowledge about early stimulation of toddler development (aged 12-59 months) in a fairly good category in the Work Area of ​​the Kenali Besar Health Center in Jambi City in 2020. Conclusion: Based on the research results, it can be concluded that parents' knowledge about early stimulation can affect the development of toddlers Keywords: Knowledge, Developmental Stimulation, Toddler